A new approach to facilitating attentional disengagement from food cues in unsuccessful dieters: The bouncing image training task. (September 2019) - Jonker, Nienke C.; Heitmann, Janika; Ostafin, Brian D.; MacLeod, Colin; Glashouwer, Klaske A.; de Jong, Peter J.
Abstract: This study tested the capacity of a modified Bouncing Image Training Task (BITT) to enhance unsuccessful dieters' attentional disengagement from food cues. Unsuccessful dieters were assigned to a training group performing daily BITT sessions for one week ( n  = 57) or a waitlist control group ( n  = 56). Change in attention was assessed using a visual search task and an odd-one-out task. Impact of the BITT on food craving and food intake were also assessed. Participants in the training group, compared to waitlist controls, showed reduced attention to food cues from pre-to post-training. Moreover, the reduction in AB to food cues exhibited by those who completed the BITT reflected the relative facilitation of attentional disengagement from food cues, rather than a reduction in attention engagement with food cues. The groups did not differ on food craving or intake post-training. It is concluded that the BITT is a promising procedure for directly manipulating individuals' attentional disengagement from food cues, though its capacity to enhance dieting success has not yet been established. Highlights: BITT training reduced attention to food cues in unsuccessful dieters. BITT training selectively altered attentional disengagement from food cues. In current form BITT training did not change unsuccessful dieters' eating behavior.